Upaya Meningkatkan Kebugaran Jasmani Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw - Wulandari, Wulandari; Jariono, Gatot (Jurnal Porkes, 2022)
The results of this study indicate that the use of the Jigsaw type of cooperative learning model has a positive impact on improving students' physical fitness learning outcomes. The research method used is Classroom Action Research (CAR) with 18 students in Class IV as the subject. Based on the results of the research data, it can be concluded: (1) The initial data is known before the action is given, it can be explained that the majority of students have not shown learning outcomes with a percentage of learning completeness 0% with a total of 0 students, or students who get scores in a good category in the range of values 80-89 with completeness criteria as many as 0 students (0%), students who obtained scores in the sufficient category in the range of values 70-79 in the sufficient category with completeness criteria as many as 0 students (0%) while students who did not complete as many as 18 students with grades percentage of 100% or each in the range of values from 60 to 69 in the poor category as many as 8 students (44%) and students in the range of values < 60 in the less category as many as 10 students (56%) and no students in the very good category with value range 90-100. (2) In Cycle I, the average score of learning outcomes was 70.94, there were 11 students (61%) completed, and 7 students (33%) had not. (3) In Cycle II, the average score of the pilot test was 81.82, there were 18 students (100%) completed and 0 students (0%) incomplete. It increased from 0% at the initial condition, to 61% at the end of cycle I and increased to 100% at the end of cycle II. Thus this proves that the application of the jigsaw type of cooperative learning model has a positive effect on increasing students' willingness to exercise.